Assembly and activation of the NLRP3 inflammasome and cytokine quantification in response to exercise in adults with different metabolic conditions: a systematic review - Cristerna-Huerta, Salma Verenice; Vega-Burgueño, Melissa; Vergara-Jiménez, Marcela de Jesús; Martínez-López, Erika; Barrón-Cabrera, Elisa (Frontiers in Sports and Active Living, 2025)
BackgroundThe NLRP3 inflammasome is a molecular structure involved in inflammation and innate immune response, its overexpression has been associated with the development of several diseases. Physical exercise plays an important role in regulating systemic inflammation, however different types of exercise seem to have a different effect in the regulation of the NLRP3 inflammasome.ObjectiveTo provide updated information related to the effect of different types and training durations of exercise on NLRP3 inflammasome complex, IL-1β—IL-18 cytokines quantification in adults with different metabolic conditions.MethodsThe Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology for manuscript research and preparation was followed using PubMed, Science Direct, SpringerLink, Scopus and Google Scholar databases for literature review. Out of 1,514 articles identified, only 11 articles fulfilled the inclusion criteria.ResultsModerate-intensity aerobic exercise and moderate resistance exercise seems to significantly decreased concentrations of the cytokine IL-1β, NLRP3 protein and caspase-1, as well as ASC and NLRP3 gene expression. High-intensity aerobic exercise exerted the opposite effects by increasing NLRP3 gene expression and the cytokines IL-1β and IL-18.ConclusionResistance, aerobic and combined exercise (≥8 weeks) were linked to downregulated key NLRP3 inflammasome components across diverse populations. These results support exercise as a safe and effective strategy to modulate NLRP3-driven inflammation. Notably, evidence suggest that resistance and combined modalities showed superior efficacy in reducing both gene and cytokine levels. This positions structured exercise as a valuable tool in managing chronic low-grade inflammation.